Avaliação de sistemas individuais de disposição de esgotos e das empresas limpa-fossas na Região Metropolitana de Goiânia - RIOS, Fernanda Posch (2010)
The system collects sewage from the city of Goiânia, capital of Goiás state, has more than 2500 km of collection network, which discharges into the sewer interceptors deployed on the banks of major watercourses in the city. About 82% of the population of this capital is serviced with sanitary sewer collection system, which the distance from the reality of the Metropolitan area of Goiânia, constituted the main city, Goiânia, comprising twelve municipal districts: Abadia de Goiás, Aparecida de Goiânia, Aragoiânia, Bela Vista de Goiás, Goianápolis, Goianira, Guapó, Hidrolândia, Nerópolis, Santo Antônio de Goiás, Senador de Goiás and Trindade. The Metropolitan area of Goiânia and the rest of the country lack accurate information about the constructive and maintenance aspects of individual systems of sanitary sewage treatment and sanitary sewage disposal, whether as a septic tank or as an onsite sewage facility. The quality and the number of on-site sewage cleaning service companies, their operational procedures, their workers conditions as well as their equipments are also unknown to people. Considering all that, the present work aims to evaluate the constructive and maintenance aspects of individual systems of sanitary sewage treatment and sanitary sewage disposal as well as to make a diagnosis of the performance of on-site sewage cleaning service companies that serve the Metropolitan area of Goiânia. All this information is essential to set corrective measures, plans and goals in order to minimize the impacts harmful to public health and to the environment as regards to the mud displayed by the on-site sewage cleaning service companies. All of the on-site sewage cleaning service companies that serve the Metropolitan area of Goiânia were identified and visited. As an addition to the useful information, 60 services displayed among different companies were closely watched. It was also determined the average percentage of the monthly treated flow related to the sludge displayed by the on-site sewage cleaning service companies inside the Sewage Treatment Plant of Goiânia. As a result it was verified that the correct use of the septic tank system, which is recommended by NBR 7227/93, is small compared to the house units demand not yet served by the plumbing sewage disposal system. As the users show little knowledge about the aforementioned system, the type of solution most used to sanitary sewage is still the cesspool. Few companies have environmental license, and most of them are classified as micro companies and have been in the market for over five years. Just one company was a market leader throughout 2008 and 2009. All companies have not been taking special care concerning both workers and equipments hygiene. Their truck fleet are in average 30 years old and all of them were adapted to receive the metallic tank and the liquid ring pump. The average month amount of sludge coming from sewage cleaning in the Sewage Treatment Station of Goiânia is small and does not alter the final flow quality. The Sewage Treatment Station of Goiânia daily receives an average of 28 trucks, being Friday the busiest day. Despite all companies are aware of the restrictions imposed by SANEAGO as regards to not receiving material other than sanitary sewage, 44% of them realize the collection, transport and final disposal in alternative places with industrial sludge which are clearly contaminated with chrome.